1989
DOI: 10.1016/0014-5793(89)80431-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimising selective deuteration of proteins for 2D 1H NMR detection and assignment studies Application to the Phe residues of Lactobacillus casei dihydrofolate reductase

Abstract: A selectively deuterated dihydrofoiate reductase from L. cusei has been prepared containing partially deuterated aromatic amino acids. This provides simplified 2D NMR spectra and allows signals from all 8 Phe residues to be identified. The pattern of deuteration is such that (i) the only cross-peaks detected in the aromatic region of the 2D COSY spectrum are those between the Phe 2',6' and 3',5' protons and (ii) chemical shift degeneracy in the aromatic region is removed thus allowing unambiguous assignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Various methods for ring deuteration of phenylalanine and tyrosine derivatives, generally employing acid catalysis, have been reported in the literature. 7f–g,15 Palladium-catalyzed ortho functionalization of aromatic amino acids such as phenylalanine and tyrosine and their derivatives has been conducted 16 but typically uses methyl esters 17 or sulfonamides 18 to efficiently direct C-H activation. It was found that simple unmodified α-phenylglycine 18 and phenylalanine 19 were deuterated selectively at the ortho positions by the developed catalytic method (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods for ring deuteration of phenylalanine and tyrosine derivatives, generally employing acid catalysis, have been reported in the literature. 7f–g,15 Palladium-catalyzed ortho functionalization of aromatic amino acids such as phenylalanine and tyrosine and their derivatives has been conducted 16 but typically uses methyl esters 17 or sulfonamides 18 to efficiently direct C-H activation. It was found that simple unmodified α-phenylglycine 18 and phenylalanine 19 were deuterated selectively at the ortho positions by the developed catalytic method (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that simple unmodified α-phenylglycine 18 and phenylalanine 19 were deuterated selectively at the ortho positions by the developed catalytic method (Scheme 3). Previously, aromatic deuterium incorporation ortho to the side chain of phenylalanine was achieved by selective protonation of ring-perdeuterated tyrosine followed by reduction to phenylalanine, 15c an inefficient and deuterium-uneconomical strategy. However, palladium-catalyzed ortho deuteration was not as effective for tyrosine 20 , and electrophilic H-D exchange by CF 3 COOD was predominant.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have examined a selectively deuterated enzyme sample incorporating the deuterated aromatic amino acids I -IV (shown in Fig. 1) chosen so that the only cross-peaks remaining in the aromatic region of the COSY spectra are those involving the Ha132 and H~1,&2 protons in the Phe residues (IV) [30]. Fig.…”
Section: Assignment Of the Phe Resonancesmentioning
confidence: 99%
“…For larger proteins selective deuteration has often been used to simplify the 'H spectra prior to using two dimensional correlation spectroscopy (2D COSY), relayed coherence transfer spectroscopy (RELAY) and homonuclear Hartmann-Hahn spectroscopy (HOHAHA) correlation experiments to make the initial assignments to residue types [25,27 -301. By careful choice of the deuteration pattern one can also simplify two dimensional nuclear Overhauser effect spectroscopy (NOESY) spectra so that unambiguous connections can be made between the remaining protons in the molecule [30]. For proteins which are too large to assign by using the direct sequential assignment method, the NOE data can be used in conjunction with available crystallographic structural information to allow specific assignments to be made [31, 321.…”
mentioning
confidence: 99%